Effects of different dietary protein levels on intestinal aquaporins in weaned piglets. Issue 2 (19th May 2022) - Ren, Zhihua; Zhang, Xinyue; Fan, Haoyue; Yu, Yueru; Yao, Shuhua; Wang, Yuqian; Dong, Yanqiang; Deng, Huidan; Zuo, Zhicai; Deng, Youtian; Wang, Ya; Xu, Zhiwen; et al.
Abstract: This study was conducted to investigate the relationship between changes in intestinal aquaporins (AQPs) in piglets fed diets with different protein levels and nutritional diarrhoea in piglets. Briefly, 96 weaned piglets were randomly divided into four groups fed diets with crude protein (CP) levels of 18%, 20%, 22% and 24%. The small intestines and colons of the weaned piglets were collected, and several experiments were conducted. In the small intestine, AQP4 protein expression was higher in weaned piglets fed the higher‐CP diets (22% and 24% CP) than in those fed the 20% CP diet except at 72 h ( p  < 0.01). At 72 h, the AQP4 protein expression in the small intestine was lower in the 18% group than in the other three groups ( p  < 0.01). Under 20% CP feeding, AQP2, AQP4 and AQP9 protein expression in the colons of piglets peaked at certain time points. The AQP2 and AQP4 mRNA levels in the colon and the AQP4 and AQP4 mRNA levels in the distal colon were approximately consistent with the protein expression levels. However, the AQP9 mRNA content in the colon was highest in the 18% group, and the AQP2 mRNA content in the distal colon was significantly higher in the 24% group than in the 20% group. AQP2 and AQP4 were expressed mainly around columnar cells in the upper part of the smooth colonic intestinal villi, and AQP9 was expressed mainly on columnar cells and goblet cells in the colonic mucosa. In conclusion, 20% CP is beneficial to the normal expression of AQP4 in the small intestine, AQP2, AQP4 and AQP9 in the colon of weaned piglets, which in turn maintains the balance of intestinal water absorption and secretion in piglets.